Decrease of Theta Response in Euthymic Bipolar Patients During an Oddball Paradigm - Atagün, Murat İlhan; Güntekin, Bahar; Özerdem, Ayşegül; Tülay, Emine Elif; BAŞAR, EROL (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2013)
Theta oscillations are related to cognitive functions and reflect functional integration of frontal and medial temporal structures into coherent neurocognitive networks. This study assessed event-related theta oscillations in medication-free, euthymic patients with bipolar disorder upon auditory oddball paradigm. Twenty-two DSM-IV euthymic bipolar I (n = 19) and II (n = 3) patients and twenty-two healthy subjects were included. Patients were euthymic for at least 6 months, and psychotropic-free for at least 2 weeks. EEG was recorded at 30 electrode sites. Auditory oddball paradigm and sensory stimuli were used. Event-related Oscillations were analyzed using adaptive filtering in two different theta frequency bands (4-6 Hz, 6-8 Hz). In healthy subjects, slow theta (4-6 Hz) responses were significantly higher than those of euthymic patients upon target, non-target and sensory stimuli (p < 0.05). Fast theta (6-8 Hz) responses of healthy subjects were significantly higher than those of euthymic patients upon target-only stimuli (p < 0.05). Reduced theta oscillations during auditory processing provide strong quantitative evidence of activation deficits in related networks in bipolar disorder. Fast theta responses are related to cognitive functions, whereas slow theta responses are related to sensory processes more than cognitive processes.
Keywords: bipolar disorder; event related oscillations; oddball; theta; theta oscillations; medication-free; euthymia; cognitive dysfunction; bipolar bozukluk; olaya bağlı salınımlar; acayip kimse; teta; teta salınımları; ilaç içermeyen; bilişsel işlev bozukluğu